PELAKSANAAN MUTASI PEGAWAI DI BADAN LINGKUNGAN HIDUP, KEBERSIHAN DAN PEMADAM KEBAKARAN KABUPATEN SANGGAU - Fahrudin E.21110094 (FISIP Universitas Tanjungpura, 2013)
he problem in this study were 1) Placement in positions of civil servants still based on competence, and 2) has not been oriented personnel system Merit System. The results showed that 1) The process of mutation is performed in the District BLHKPK've noticed the rules that apply. A civil servant in the mutation when it meets the requirements set in legislation staffing. An employee who transferred assessed competence, work performance, and the level of the rank of a civil servant. Mutation is done at least 2 times a year. And 2) Basic Principles of Civil mutations targeting the professionalism, competence, performance and ranks it is intended that the achievement of the organization's performance BLHKPK the District for the better. Addressing the phenomenon that there is intense communication should be done by a team with Regent Sanggau Baperjakat. To be able to bring up Baperjakat trial could run smoothly. Besides good communication also needs to be built between the Regent and Vice Regent due to mutation of a civil servant also need to consider the suggestions and proposals of Vice Regent. And the last suggestion Baperjakat team should really pay attention to the background of civil servants (PNS) when you want to put a civil servant in an office.Keywords: Movements, Civil Servants